Letter - Hinsley, Arthur, 1894-1968
806-0001-001 Labour Catholic Vote ARCHBISHOP'S HOUSE, WESTMINSTER, LONDON, S.W.1. April 5th. 1939. Dear Dr. Morgan, Thank you for your interesting letter of 3rd. which is most consoling. It is good to know that the really social work of the Church in the West Indies, inspired by and based on religion, is recognised. I know already something of the work of St. Mary's College, Trinidad. But I must stress the need of all really Catholic work being done on non-party lines. Therefore, I can take no part in political organisation as such, but only urge the observance of moral and religious principles in any and every party. With every best wish, Yours sincerely in Christ, A. Cardinal Hinsley Archbishop of Westminster. H.B. Morgan, Esq. M.D., 4, Aberdare Gardens, Hampstead, London, N.W.6. 292C/806.1/1/1